Quantum information science and technology professional learning for secondary science, technology, engineering, and mathematics teachers - Angela M. Kelly; Michele Darienzo; Tzu-Chieh Wei; Dominik Schneble (Physical Review Physics Education Research)
[This paper is part of the Focused Collection in Investigating and Improving Quantum Education through Research.] There is a growing need in the United States for a workforce trained in quantum information science and technology (QIST), a disciplinary topic that is rarely addressed in precollege science, mathematics, and computer science curricula. University quantum physics and physics education researchers designed and initiated a 4-week, 12-h QIST professional development workshop for N=51 preservice and in-service secondary school science, mathematics, and computer science educators. A STEM integration framework guided the workshop structure, which incorporated a situated cognition model for learning quantum concepts and computing, identifying recent advances in quantum technologies, planning curricula, and differentiating among QIST subfields including quantum communication, quantum computation, quantum simulation, and quantum metrology and sensing. The pre-/post-research design employed a newly developed teacher attitude survey, Teacher Self-Efficacy in Quantum Information Science and Technology Scale (TSE-QIST). Exploratory factor analysis identified three latent constructs in teachers’ self-efficacy, including (i) knowledge about QIST academic pathways and careers; (ii) QIST pedagogical fluency and STEM integration; and (iii) facilitating QIST learning. Parametric comparisons of means indicated that teacher participants showed significant gains overall and in all latent constructs with medium to large effect sizes (p<0.001). This professional learning model shows promise in strengthening teachers’ self-confidence in pedagogical content knowledge of quantum ideas so they may facilitate student engagement in quantum information science, a field that involves conceptual change and is often considered abstract, counterintuitive, inaccessible, and suitable only for the academically elite. Implications for policy and practice are discussed.